Preparation method and application of composite coating with micro-nano structure
By constructing a composite coating of micro-nano structures in the coating, using electrospinning and magnetron sputtering technology, the problem of degradation of traditional coatings after wear is solved, achieving efficient and precise coating deposition and excellent comprehensive performance.
Patent Information
- Application Number
- CN202411710714.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
After the existing layered coating is worn, the lower coating cannot fully perform its due function, resulting in a reduced overall utilization rate of the coating and limited service life and functional performance.
The composite coating preparation method of micro-nano structures is used to prepare fibrous structures through electrospinning technology, and the titanium nitride and carbon lubricating coatings are deposited using magnetron sputtering technology to form a composite coating with a unique micro-nano structure.
It achieves efficient and precise deposition of the coating, breaks through the limitations of traditional layered coatings "failure once worn", greatly improves the overall performance of the coating, extends the service life and improves functional performance.
Smart Images

Figure CN119530737A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a preparation method and application of a composite coating with a micro-nano structure. Background Art
[0002] With the rapid development of modern manufacturing, the demand for high-performance tools continues to grow. Among these tools, coating technology, as a key means to improve durability and performance, has become increasingly important. In many key fields such as mechanical processing, aerospace, and automobile manufacturing, the efficient and precise operation of high-performance tools is directly related to production efficiency and product quality. Therefore, the development of coating technology with excellent wear resistance, corrosion resistance, and specific functionality will not only help extend the service life of the tool, but also significantly improve processing accuracy and reduce production costs.
[0003] In traditional layered coating designs, friction and wear of the coating usually start from the top layer. When the upper layer of the coating is worn, the lower layer of the coating often cannot fully perform its functions, or may even lose its functions completely. This structural pattern of layered coatings leads to a significant reduction in the comprehensive utilization rate of the coating, thus affecting its overall performance. In addition, since the coating cannot maintain the synergistic functions of the multi-layer coating at the same time after wear, the service life and functional performance of the coating will be significantly limited. Summary of the invention
[0004] The embodiments of the present application provide a method for preparing and applying a composite coating with a micro-nano structure, thereby solving the technical problem in the prior art that the lower coating cannot fully perform its due function after the upper coating in the layered coating is worn away.
[0005] In a first aspect, an embodiment of the present application provides a method for preparing a micro-nanostructured composite coating, the method comprising:
[0006] Cutting the cemented carbide sample into desired sizes to prepare a substrate;
[0007] preparing an electrospinning mask;
[0008] An electrospinning mask is covered on the surface of a substrate, and a coating deposition operation is performed on the substrate covered by the electrospinning mask using a magnetron sputtering device to obtain a composite coating with a micro-nano structure; wherein the deposited material is at least one of metal, ceramic, alloy and non-metal.
[0009] In combination with the first aspect, in a possible implementation, cutting the cemented carbide sample into a desired size to obtain a substrate includes:
[0010] The cemented carbide samples were cut to the required size using wire cutting technology;
[0011] The surface of the cut cemented carbide sample is mechanically ground using water sandpaper to remove the oxide layer and impurities on the surface;
[0012] The mechanically ground cemented carbide sample was placed in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning in turn, each cleaning time was 15-20 minutes, and then it was blown dry with cold air to obtain a substrate.
[0013] In combination with the first aspect, in a possible implementation manner, the substrate is a round wafer with a diameter of 25 mm and a thickness of 3 mm.
[0014] In combination with the first aspect, in a possible implementation manner, preparing an electrospinning mask includes:
[0015] preparing an electrospinning solution;
[0016] The electrospinning technology is adopted to spin the prepared electrospinning solution on a metal ring through a spinning device to form a desired electrospinning mask.
[0017] In combination with the first aspect, in a possible implementation, preparing an electrospinning solution includes:
[0018] Weigh 0.343 g of polyvinyl pyrrolidone powder and add it in small amounts to a beaker containing 5 ml of ethanol, while covering the beaker with plastic wrap to prevent ethanol from volatilizing, to obtain a mixed solution;
[0019] The mixed solution was stirred using a magnetic stirrer for 30 min until the polyvinyl pyrrolidone powder was completely dissolved in the ethanol to obtain the desired electrospinning solution.
[0020] In combination with the first aspect, in a possible implementation, an electrospinning technique is used to spin the prepared electrospinning solution on a metal ring through a spinning device to form a desired electrospinning mask, including:
[0021] The fiber structure on the electrospinning mask has micro-nano characteristics. The voltage of electrospinning is 8-12KV, the spinning distance is 10-15CM, and the density of the electrospinning solution is adjusted;
[0022] The distribution density and morphology of the fibers on the electrospinning mask are controlled to ensure that the microstructure of the electrospinning mask matches the microstructure required for the composite coating.
[0023] In combination with the first aspect, in a possible implementation manner, the diameter of the fiber ranges from 300 nanometers to 2 micrometers.
[0024] In combination with the first aspect, in a possible implementation, an electrospinning mask is covered on the surface of a substrate, and a coating deposition operation is performed on the substrate covered by the electrospinning mask using a magnetron sputtering device to obtain a composite coating having a micro-nano structure, wherein the coating deposition process includes:
[0025] Titanium nitride coating was magnetron sputtered on the substrate covered by the electrospinning mask using a magnetron sputtering device. During this process, argon was used as a protective sputtering condition gas. The RF power of the magnetron sputtering device was set to 110W-130W, the working pressure was 0.5Pa, and the vacuum degree was 7.5×10 -4 Pa, the deposition time was 2-2.5 h, and the deposition temperature was 200 °C to obtain a sample with titanium nitride coating;
[0026] The sample with the titanium nitride coating is taken out, and the electrospinning mask therein is removed to obtain a substrate with fiber grooves on the surface;
[0027] The magnetron sputtering equipment was used again to perform magnetron sputtering on the substrate with fiber grooves to deposit the carbon lubricating coating. During this process, argon was used as the protective sputtering condition gas. The DC power of the magnetron sputtering equipment was set to 50-70W, the working pressure was 0.5Pa, and the vacuum degree was 7.5×10 -4 Pa, the deposition time is 1-1.5h, the deposition temperature is 400°C, and a composite coating with a micro-nano structure is obtained.
[0028] In the second aspect, an embodiment of the present application provides an application of a micro-nanostructured composite coating, including a method for preparing the micro-nanostructured composite coating described in the first aspect or any possible implementation of the first aspect, and applying the micro-nanostructured composite coating to the surface of cutting tools, wear-resistant mechanical parts, electronic devices and biomedical devices.
[0029] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects:
[0030] The embodiment of the present application provides a method for preparing a composite coating with a micro-nano structure. The present application combines the advantages of electrospinning technology and magnetron sputtering technology to achieve efficient and accurate coating deposition. The resulting composite coating has a unique micro-nano structure, which is composed of a fibrous structure formed by electrospinning technology and nanoparticles, nanocolumns or nanofilms generated by magnetron sputtering technology. By constructing a micro-nano structure inside the coating, a uniform filling space is successfully reserved in the coating, so that a variety of functional materials can be evenly distributed and work together. This innovative design not only breaks through the limitation of traditional layered coatings that "fail once worn", but also shows outstanding results in significantly improving the overall performance of the coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following is a brief introduction to the drawings required for use in the description of the embodiments of the present application. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0032] Figure 1 A schematic diagram of the structure of a spinning device provided in an embodiment of the present application;
[0033] Figure 2 A schematic diagram of the structure of a magnetron sputtering device provided in an embodiment of the present application;
[0034] Figure 3 A schematic diagram of the structure of a composite coating with a micro-nano structure provided in an embodiment of the present application;
[0035] Figure 4 for Figure 3 100 times magnified image;
[0036] Figure 5 A flow chart of a method for preparing a micro-nanostructured composite coating provided in an embodiment of the present application;
[0037] Figure 6 A schematic diagram of the preparation process of the micro-nanostructured composite coating provided in an embodiment of the present application.
[0038] Icons: 1-spinning device; 2-magnetron sputtering equipment; 3-electrospinning mask; 4-composite coating with micro-nano structure; 5-substrate. DETAILED DESCRIPTION
[0039] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0040] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship indicated by the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside", "outside", etc. is based on the orientation or positional relationship shown in the drawings, and is only for the convenience of describing the embodiments of the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. The terms "first", "second", and "third" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance. In addition, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0041] The present application provides a method for preparing a micro-nanostructured composite coating. Figure 1-Figure 6 The method comprises steps S1-S3:
[0042] S1: Cut the cemented carbide sample into a desired size to obtain a substrate 5.
[0043] S2: preparing electrospinning mask 3.
[0044] S3: Cover the surface of the substrate 5 with the electrospinning mask 3, and use the magnetron sputtering device 2 to perform a coating deposition operation on the substrate 5 covered by the electrospinning mask 3 to obtain a composite coating 4 with a micro-nano structure. The deposition material is at least one of metal, ceramic, alloy and non-metal.
[0045] It should be noted that the present application combines the advantages of electrospinning technology and magnetron sputtering technology to achieve efficient and precise coating deposition. The resulting composite coating has a unique micro-nano structure, which is composed of a fibrous structure formed by electrospinning technology and nanoparticles, nanocolumns or nanofilms generated by magnetron sputtering technology. By constructing a micro-nano structure inside the coating, a uniform filling space is successfully reserved in the coating, so that a variety of functional materials can be evenly distributed and work together. This innovative design not only breaks through the limitation of traditional layered coatings that "fail once worn", but also shows outstanding results in significantly improving the overall performance of the coating.
[0046] In the embodiment of the present application, the cemented carbide sample is cut into a desired size to obtain the substrate 5, including steps S101-S103:
[0047] S101: Cut the cemented carbide sample to the required size using wire cutting technology.
[0048] S102: The surface of the cut cemented carbide sample is mechanically ground using water sandpaper to remove the oxide layer and impurities on the surface.
[0049] It should be noted that the present application uses water sandpaper to mechanically grind the surface of the cut cemented carbide sample to effectively remove the surface oxide layer and impurities, which not only improves the flatness of the surface of the substrate 5, but also reduces the coating quality problems caused by surface defects, such as insufficient coating adhesion and uneven coating thickness.
[0050] S103: The mechanically ground cemented carbide sample is sequentially placed in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning, each cleaning time being 15-20 minutes, and then blown dry with cold air to obtain a substrate 5.
[0051] It should be noted that the present application deeply cleans the cemented carbide sample after mechanical grinding by ultrasonic cleaning and cold air drying. The use of acetone, anhydrous ethanol and deionized water in sequence can completely remove pollutants such as grease and dust on the surface of the sample to ensure the cleanliness of the surface of the substrate 5. At the same time, cold air drying avoids the influence of residual moisture on the coating quality and provides a clean and dry substrate 5 surface for subsequent coating deposition.
[0052] After the above processing steps, the surface quality of the substrate 5 of the present application has been significantly improved, which provides favorable conditions for the subsequent coating deposition operation. The high-quality surface of the substrate 5 can improve the adhesion, uniformity and wear resistance of the coating, thereby extending the service life of the coating and enhancing the overall performance of the coating. A clean and flat surface of the substrate 5 helps to form a close bond between the coating and the substrate 5, thereby improving the adhesion of the coating, which is of great significance for improving the stability and durability of the coating in complex environments.
[0053] In the embodiment of the present application, the substrate 5 is a round wafer with a diameter of 25 mm and a thickness of 3 mm.
[0054] In the embodiment of the present application, the electrospinning mask 3 is prepared, including steps S201-S202:
[0055] S201: Prepare the electrospinning solution to ensure that it meets the requirements of the spinning process.
[0056] S202: Using electrospinning technology, the prepared electrospinning solution is spun on a metal ring through a spinning device 1 to form a desired electrospinning mask 3. The shape of the metal ring is perfectly matched with the substrate 5. As a supporting structure, it can not only maintain the stability and morphology of the fiber, but also ensure the close fit between the electrospinning mask 3 and the substrate 5.
[0057] Specifically, the spinning can evenly cover the metal ring to form a continuous and dense fiber network. This uniformity is crucial because it ensures that the deposited material can be accurately distributed in the area covered by the electrospinning mask 3 during the coating deposition process, thereby significantly improving the uniformity and consistency of the coating. In addition, the close combination between the electrospinning mask 3 and the metal ring, and the staggered connection between the fibers inside the electrospinning mask 3, enhance the adhesion between the coating and the substrate 5. This tight structural design not only improves the durability of the coating, but also significantly enhances its wear resistance.
[0058] In the embodiment of the present application, preparing the electrospinning solution includes steps S2011-S2012:
[0059] S2011: Weigh 0.343 g of polyvinyl pyrrolidone powder and add it in small amounts to a beaker containing 5 ml of ethanol, while covering the beaker with plastic wrap to prevent ethanol from volatilizing, to obtain a mixed solution.
[0060] S2012: The mixed solution was stirred using a magnetic stirrer for 30 minutes until the polyvinyl pyrrolidone powder was completely dissolved in the ethanol to obtain the desired electrospinning solution.
[0061] It should be noted that the use of a magnetic stirrer not only improves the dissolution efficiency, but also promotes uniform mixing within the solution, providing a high-quality spinning solution for the subsequent electrospinning process. The obtained electrospinning solution has a suitable concentration and viscosity, which is crucial for the stability of the electrospinning process and the control of fiber quality. A high-quality spinning solution helps to prepare nanofibers with uniform diameter and good morphology.
[0062] Specifically, by transferring the prepared electrospinning solution into a syringe, the flow rate and spinning speed of the solution can be easily controlled, thereby achieving precise control of the fiber diameter and morphology. In addition, as a commonly used liquid transfer tool, the syringe has the advantages of being easy to operate, easy to clean and reusable.
[0063] In the embodiment of the present application, an electrospinning technique is used to spin the prepared electrospinning solution on a metal ring through a spinning device 1 to form a desired electrospinning mask 3, including steps S2021-S2022:
[0064] S2021: The fiber structure on the electrospinning mask 3 has micro-nano characteristics. The voltage of electrospinning is 8-12KV and the spinning distance is 10-15CM. This parameter optimization helps to form stable and continuous fibers, reduce the uncertainty in the spinning process, and improve the quality of the electrospinning mask 3. By adjusting the density of the electrospinning solution, the diameter, morphology and distribution of the fibers can be further controlled.
[0065] S2022: Control the distribution density and morphology of the fibers on the electrospinning mask 3 to ensure that the microstructure of the electrospinning mask 3 matches the microstructure required for the composite coating, providing strong support for the deposition and performance optimization of the subsequent coating.
[0066] In the embodiment of the present application, the diameter of the fiber ranges from 300 nanometers to 2 microns. The electrospinning mask 3 with a fiber diameter in the range of 300 nanometers to 2 microns helps to form a tighter interface between the coating and the substrate 5, which enhances the bonding force between the coating and the substrate 5 and improves the adhesion and durability of the coating.
[0067] In the embodiment of the present application, the electrospinning mask 3 is covered on the surface of the substrate 5, and the magnetron sputtering device 2 is used to perform a coating deposition operation on the substrate 5 covered by the electrospinning mask 3 to obtain a composite coating 4 with a micro-nano structure, wherein the coating deposition process includes steps S301-S303:
[0068] S301: magnetron sputtering titanium nitride coating on substrate 5 covered by electrospinning mask 3 by magnetron sputtering device 2. In this process, argon gas is used as protective sputtering condition gas. The RF power of magnetron sputtering device 2 is set to 110W-130W, the working pressure is 0.5Pa, and the vacuum degree is 7.5×10 -4 Pa, the deposition time is 2-2.5h, the deposition temperature is 200℃, and a sample with titanium nitride coating is obtained.
[0069] During the magnetron sputtering process, argon is ionized into argon ions. These ions are accelerated under the action of the electric field and bombard the surface of the target material (such as titanium nitride), causing the target atoms or molecules to be sputtered out and then deposited on the substrate 5. Since argon is an inert gas, its chemical properties are stable and it is not easy to react with other substances. Therefore, during the sputtering process, argon can effectively protect the target material and substrate 5 from adverse effects such as oxidation and contamination. In addition, the presence of argon can also improve the crystallinity and density of the coating, thereby improving the quality and mechanical strength of the coating. At the same time, argon also helps to reduce pores and defects in the coating, thereby improving the corrosion resistance and wear resistance of the coating.
[0070] Specifically, the RF power of the magnetron sputtering device 2 of the present application is set to 120 W, and the deposition time is 2 h.
[0071] S302: Take out the sample with the titanium nitride coating, and remove the electrospinning mask 3 therein, to obtain a substrate 5 with fiber grooves on the surface.
[0072] S303: The magnetron sputtering device 2 is used again to perform magnetron sputtering on the substrate 5 with the fiber grooves to deposit the carbon lubricating coating. In this process, argon gas is used as the protective sputtering condition gas. The DC power of the magnetron sputtering device 2 is set to 50-70W, the working pressure is 0.5Pa, and the vacuum degree is 7.5×10 -4 Pa, the deposition time is 1-1.5h, the deposition temperature is 400°C, and a composite coating 4 with a micro-nano structure is obtained.
[0073] Specifically, the DC power of the magnetron sputtering device 2 of the present application is set to 60 W, and the deposition time is 1 hour.
[0074] It should be noted that the present application utilizes the electrospinning mask 3 to precisely control the fiber groove structure on the surface of the substrate 5, thereby providing an ideal template for subsequent coating deposition. Under the cover of the electrospinning mask 3, a layer of titanium nitride (TiN) coating is first deposited on the substrate by magnetron sputtering technology. After the titanium nitride coating is formed, the electrospinning mask 3 is removed, and the magnetron sputtering technology is used again to deposit a layer of carbon lubricating coating, so that the carbon lubricating material is evenly filled into the micro-nano structure previously formed by the electrospinning mask 3.
[0075] In this process, the titanium nitride coating significantly improves the wear resistance and service life of the substrate 5 with its high hardness, high wear resistance and corrosion resistance. The carbon lubricating coating reduces the friction coefficient between the coating and the friction surface, improves the lubrication performance of the coating, and thus reduces wear and energy consumption. In addition, the fiber groove structure ensures the uniform distribution of the coating, avoiding the problem of local over-thickness or over-thinness that may occur in traditional coatings. At the same time, these grooves provide more interface area, promote the close bonding between the coating and the substrate 5, thereby improving the adhesion and durability of the coating.
[0076] The embodiment of the present application innovatively combines electrospinning technology and magnetron sputtering technology to achieve precise control of the coating structure and optimization of performance. Specifically, the method first uses electrospinning technology to prepare an electrospinning mask 3 with a fiber structure having micro-nano characteristics, which provides a basis for the subsequent filling of functional materials. Subsequently, a titanium nitride (TiN) coating with an intra-layer fiber structure is prepared by magnetron sputtering technology, and a carbon lubricating coating is accurately deposited in these fiber grooves, finally forming a composite coating that combines a titanium nitride coating with high hardness, good corrosion resistance and high temperature stability with a carbon lubricating coating with a low friction coefficient, excellent wear resistance and lubrication performance, giving the coating excellent comprehensive performance.
[0077] The embodiments of the present application provide an application of a micro-nanostructured composite coating, including a method for preparing the above-mentioned micro-nanostructured composite coating, and applying the micro-nanostructured composite coating to the surface of cutting tools, wear-resistant mechanical parts, electronic devices and biomedical devices.
[0078] First, in the field of cutting tools, the titanium nitride (TiN) component in the micro-nanostructured composite coating significantly improves the hardness of the cutting tool with its extremely high hardness and wear resistance, thereby extending its service life. At the same time, the addition of the carbon lubricating coating further reduces friction and wear during the cutting process, further improving the durability of the tool.
[0079] Secondly, in terms of wear-resistant mechanical parts, the titanium nitride and carbon lubricating coating in the composite coating work together to significantly improve the wear resistance of the parts, effectively reduce equipment failures and downtime caused by wear, and reduce maintenance costs.
[0080] In addition, in the field of electronic devices, micro-nanostructured composite coatings can optimize the conductivity and heat dissipation of the device surface, thereby improving the performance and stability of the device, providing a strong guarantee for the reliable operation of electronic equipment.
[0081] Finally, in terms of biomedical devices, composite coatings have excellent anti-corrosion and antibacterial properties, which can protect devices from contamination and erosion by microorganisms, significantly reduce the risk of infection, and provide strong support for the safety and health of patients.
[0082] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other. Each embodiment focuses on the differences from other embodiments.
[0083] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A method for preparing a micro-nanostructured composite coating, characterized in that: The method includes: Cutting the cemented carbide sample into desired sizes to prepare a substrate; preparing an electrospinning mask; An electrospinning mask is covered on the surface of a substrate, and a coating deposition operation is performed on the substrate covered by the electrospinning mask using a magnetron sputtering device to obtain a composite coating with a micro-nano structure; wherein the deposited material is at least one of metal, ceramic, alloy and non-metal.
2. The method for preparing a micro-nanostructured composite coating according to claim 1, characterized in that: The cemented carbide samples were cut into the required size to prepare the substrate, including: The cemented carbide samples were cut to the required size using wire cutting technology; The surface of the cut cemented carbide sample is mechanically ground using water sandpaper to remove the oxide layer and impurities on the surface; The mechanically ground cemented carbide sample was placed in acetone, anhydrous ethanol and deionized water for ultrasonic cleaning in turn, each cleaning time was 15-20 minutes, and then it was blown dry with cold air to obtain a substrate.
3. The method for preparing a micro-nanostructured composite coating according to claim 1, characterized in that: The substrate is a disc with a diameter of 25 mm and a thickness of 3 mm.
4. The method for preparing a micro-nanostructured composite coating according to claim 3, characterized in that: Preparing an electrospinning mask, comprising: preparing an electrospinning solution; The electrospinning technology is adopted to spin the prepared electrospinning solution on a metal ring through a spinning device to form a desired electrospinning mask.
5. The method for preparing a micro-nanostructured composite coating according to claim 4, characterized in that: Prepare the electrospinning solution, including: Weigh 0.343 g of polyvinyl pyrrolidone powder and add it in small amounts to a beaker containing 5 ml of ethanol, while covering the beaker with plastic wrap to prevent ethanol from volatilizing, to obtain a mixed solution; The mixed solution was stirred using a magnetic stirrer for 30 min until the polyvinyl pyrrolidone powder was completely dissolved in the ethanol to obtain the desired electrospinning solution.
6. The method for preparing a micro-nanostructure composite coating according to claim 4, characterized in that: The electrospinning technology is used to spin the prepared electrospinning solution on a metal ring through a spinning device to form a desired electrospinning mask, including: The fiber structure on the electrospinning mask has micro-nano characteristics. The voltage of electrospinning is 8-12KV, the spinning distance is 10-15CM, and the density of the electrospinning solution is adjusted; The distribution density and morphology of the fibers on the electrospinning mask are controlled to ensure that the microstructure of the electrospinning mask matches the microstructure required for the composite coating.
7. The method for preparing a micro-nanostructure composite coating according to claim 6, characterized in that: The diameter of the fibers ranges from 300 nanometers to 2 micrometers.
8. The method for preparing a micro-nanostructure composite coating according to claim 1, characterized in that: The electrospinning mask is covered on the surface of the substrate, and a coating deposition operation is performed on the substrate covered by the electrospinning mask using a magnetron sputtering device to obtain a composite coating with a micro-nano structure, wherein the coating deposition process includes: Titanium nitride coating was magnetron sputtered on the substrate covered by the electrospinning mask using a magnetron sputtering device. During this process, argon was used as a protective sputtering condition gas. The RF power of the magnetron sputtering device was set to 110W-130W, the working pressure was 0.5Pa, and the vacuum degree was 7.5×10 -4 Pa, the deposition time was 2-2.5 h, and the deposition temperature was 200 °C to obtain a sample with titanium nitride coating; The sample with the titanium nitride coating is taken out, and the electrospinning mask therein is removed to obtain a substrate with fiber grooves on the surface; The magnetron sputtering equipment was used again to perform magnetron sputtering on the substrate with fiber grooves to deposit the carbon lubricating coating. During this process, argon was used as the protective sputtering condition gas. The DC power of the magnetron sputtering equipment was set to 50-70W, the working pressure was 0.5Pa, and the vacuum degree was 7.5×10 -4 Pa, the deposition time is 1-1.5h, the deposition temperature is 400°C, and a composite coating with a micro-nano structure is obtained.
9. An application of a micro-nanostructured composite coating, characterized in that: The invention comprises the method for preparing the composite coating of the micro-nano structure by using any one of claims 1 to 8, and applying the composite coating of the micro-nano structure to the surface of cutting tools, wear-resistant mechanical parts, electronic devices and biomedical devices.